Molecular alterations of the IDH1 gene in AML: a Children’s Oncology Group and Southwest Oncology Group study - Ho, Phoenix A. (2010)
Recent whole-genome sequencing efforts led to the identification of IDH1(R132) mutations in AML patients. We studied the prevalence and clinical implications of IDH1 genomic alterations in pediatric and adult AML. Diagnostic DNA from 531 AML patients treated on Children’s Oncology Group trial COG-AAML03P1 (N=257), and Southwest Oncology Group trials SWOG-9031, SWOG-9333, and SWOG-9500 (N=274), were tested for IDH1 mutations. Codon R132 mutations were absent in the pediatric cohort, but were found in 12/274 adult patients (4.4%, 95% CI 2.3-7.5%). IDH1(R132) mutations occurred most commonly in patients with normal karyotype, and those with FLT3/ITD and NPMc mutations. Patients with IDH1(R132) mutations trended towards higher median diagnostic WBC counts (59.2 × 10(9)/L vs. 29.1 × 10(9)/L, P=0.19) than those without mutations, but the two groups did not differ significantly in age, bone marrow blast percentage, overall survival, or relapse-free survival. Eleven patients (2.1%) harbored a novel V71I sequence alteration, which was found to be a germline polymorphism. IDH1 mutations were not detected in pediatric AML, and are uncommon in adult AML.